Synthesis of bimetallic Co-Ni/ZnO nanoprisms (ZnO-NPr) for hydrogen-rich syngas production via partial oxidation of methane. Issue 6 (December 2021) - Javed, Ahad Hussain; Shahzad, Nadia; Butt, Faaz Ahmed; Khan, M. Abdullah; Naeem, Nida; Liaquat, Rabia; Khoja, Asif Hussain
Abstract: The utilisation of methane (CH4 ) to produce syngas (H2, CO) via partial oxidation of methane (POM) is an attractive technique, as syngas is a very valuable entity to produce liquid fuels and fuel cell applications. This work presents the hydrothermal growth of ZnO nanoprisms (ZnO-NPr) in a dual solvent for a controlled structure. The Co-Ni loaded ZnO-NPr catalysts were obtained in an aqueous solution by wetness impregnation method and tested for POM for the first time. The synthesized catalysts were characterized by employing XRD, SEM-EDX, TGA and RAMAN spectroscopy for structural and morphological analysis. The catalysts were analyzed for POM at 850 °C and demonstrated high catalytic activity. It was observed that the catalytic activity of Co loaded ZnO-NPr, and Ni-Co loaded ZnO-NPr was more and demonstrated the stable behaviour for CH4 conversion in comparison to Ni loaded catalysts. The Co-Ni loaded ZnO-NPr has shown a high CH4 conversion (XCH4 ) (98%), and excellent stability over 56 h on stream. The average value of H2 /CO for Co-Ni loaded ZnO-NPr was 2.11, above the theoretical value for POM. It is attributed to the better performance of catalyst towards the selectivity of H2 in reaction pathways. Graphical Abstract: ga1 Highlights: ZnO nanoprisms (NPr) support was successfully synthesized by hydrothermal process. Bimetallic loaded ZnO-NPr showed shape dependent support effect in POM. The high reactivity shown due to better interaction of Co and surface of support. The bimetallic loaded catalyst exhibited excellent stability in POM reaction up to 56 h.